Kuwait : 2009 Article IV Consultation; Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2009)
Kuwait's economy continued to perform strongly in 2008, although signs of weakness emerged in the second half of the year. The authorities' key challenge in the near term is to preserve financial stability and cushion the impact of the global slowdown. Executive Directors have commended the Kuwaiti authorities' prudent macroeconomic policies, which have contributed to robust economic growth, strong fiscal and external positions. Directors have also called for strengthening oversight of risk management practices by ensuring adequate policies and procedures for identifying, monitoring, and controlling systemic risk in the financial system.